2023
DOI: 10.1007/s10965-023-03834-z
|View full text |Cite
|
Sign up to set email alerts
|

‘Spider-like’ POSS in NIPU webs: enhanced thermal stability and unique swelling behavior

Izabela Łukaszewska,
Artur Bukowczan,
Konstantinos N. Raftopoulos
et al.

Abstract: PEO-based non-isocyanate polyhydroxyurethane (NIPU, PHU) networks physically modified with octa(3-hydroxy-3-methylbutyldimethylsiloxy)POSS (8OHPOSS) were synthesized via one-pot one-step approach. POSS was introduced into the polymer matrix in the amount of 1–10 wt%. Polar hydroxyls on the vertex groups of POSS allowed for uniform dispersion even up to high loadings (10 wt%). Composites exhibit enhanced thermal stability in comparison to the pristine matrix. FTIR analysis confirmed that POSS strengthens the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…NIPU networks at hand upon immersion in an aqueous medium exhibit water absorption in the range typical for hydrogels, and we have observed this kind of behavior in our previous work [56]. To study polymer-water interactions in such a system in detail, the changes in physicochemical properties of the NIPUs were monitored as a function of the environmental relative humidity (water vapor absorption).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…NIPU networks at hand upon immersion in an aqueous medium exhibit water absorption in the range typical for hydrogels, and we have observed this kind of behavior in our previous work [56]. To study polymer-water interactions in such a system in detail, the changes in physicochemical properties of the NIPUs were monitored as a function of the environmental relative humidity (water vapor absorption).…”
Section: Resultsmentioning
confidence: 73%
“…Taking also into account that there is no significant change in the energetic parameters and it may be concluded that 8OHPOSS does not hinder access of water to hydration sites and it does not “block” any of them. Although in [ 56 ] we observed some attachment of POSS on the polymer chain by hydrogen bonds, this does not hinder the attachment of the more mobile and more polar water molecules to access the hydration sites. The obtained values of monolayer capacity are around 14 g per 100 g of dry material, which is more than 25 times higher than in cellulose-based hydrogels studied by Filip et al [ 72 ], 3.5 times higher than for acrylate hydrogels reported by Ferrer et al [ 73 ], and 1.5 times the value reported for polyacrylamide-based superporous hydrogel composites reported by Mittal et al [ 74 ].…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations